2017
DOI: 10.1101/235010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The IRE1a-XBP1 pathway promotes T helper cell differentiation by resolving secretory stress and accelerating proliferation

Abstract: SummaryThe IRE1a-XBP1 pathway, a conserved adaptive mediator of the unfolded protein response, is indispensable for the development of secretory cells. It maintains endoplasmic reticulum homeostasis by facilitating protein folding and enhancing secretory capacity of the cells. Its role in immune cells is emerging. It is involved in dendritic cell, plasma cell and eosinophil development and differentiation. Using genome-wide approaches, integrating ChIPmentation and mRNA-sequencing data, we have elucidated the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Using multicolor flow cytometry ( Supplementary Figure 5), we identified significant upregulation of fBM CD11b + CD11c + pre-cDCs expressing intracellular XBP1s following maternal OM-85 treatment ( Figures 4A, B). While intracellular XBP1s expression was additionally localized within fetal B-cells, NK cells and Tcells ( Supplementary Figure 6), as previously described in the literature (39,41,42,52), maternal OM-85 treatment had no impact on XBP1s expression levels in these cell types.…”
Section: Upregulation Of Xbp1s Expression Is Restricted To Fetal Bonesupporting
confidence: 81%
See 1 more Smart Citation
“…Using multicolor flow cytometry ( Supplementary Figure 5), we identified significant upregulation of fBM CD11b + CD11c + pre-cDCs expressing intracellular XBP1s following maternal OM-85 treatment ( Figures 4A, B). While intracellular XBP1s expression was additionally localized within fetal B-cells, NK cells and Tcells ( Supplementary Figure 6), as previously described in the literature (39,41,42,52), maternal OM-85 treatment had no impact on XBP1s expression levels in these cell types.…”
Section: Upregulation Of Xbp1s Expression Is Restricted To Fetal Bonesupporting
confidence: 81%
“…Upstream regulator analysis was then performed to identify putative molecular drivers of all observed DEG. The data revealed X-box binding protein 1 (XBP1), a transcription factor central to the UPR (38) (42) and DCs (43,44), as the most strongly activated molecular driver within fBM associated with maternal OM-85 treatment effects (P-value = 3.81x10 -17 , Z-score = 4.427, Figure 3C; Supplementary Table 3), and consistent with this, its downstream target, the canonical UPR sensor Activating Transcription Factor 6 beta (ATF6b) (45,46) was upregulated (Supplementary Table 1 and Supplementary Table 3). Additionally, Endoplasmic Reticulum To Nucleus Signalling 1 (ERN1) was identified as an activated driver gene within the fBM following maternal OM-85 treatment (P-value = 3.32x10 -6 , Zscore = 2.156; Figure 3C; Supplementary Table 3).…”
Section: Maternal Om-85 Treatment Activates Key Regulators Of the Uprmentioning
confidence: 99%
“…Classification of the Th subtype is based on the production of specific cytokines and transcription factors that are important for differentiation [99]. XBP1s regulates genes that control diverse physiological aspects of Th2 cells [100]. IRE1α-XBP1s signaling controls cytokine expression, secretion, and cell proliferation in Th2 cells.…”
Section: T Cellsmentioning
confidence: 99%
“…High SEC63 expression had been shown to have involvement in apoptosis and reduced proliferation in hepatic tumors (Casper et al, 2013); ERDJ4 has been shown to have crucial role in B cell differentiation in the event of hematopoiesis (Fritz and Weaver, 2014). Besides, DNAJC3 is known to get increased during plasma cells differentiation (Shaffer et al, 2004); the expression of PDIA3 and DNAJC3 were shown to get up regulated during T-helper cell differentiation and treatment with IRE1α’s endoribonuclease activity specific inhibitor 4µ8c down regulated their expression via inhibiting XBP1 mRNA splicing (Pramanik et al, 2017). Our results suggested that expression of all these genes increased in kaempferol treated conditions, and get reversed by pretreatment with STF083010 (Fig.…”
Section: Resultsmentioning
confidence: 99%